Chain Message Game: Is It The Best Solution to Increase Student's Understanding in English Language Teaching? - Elyn Nur Wachidah; Nur Laily Amidah; Rofiq Harissa S (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2021)
This study aims to find out the truth of the application of the Chain Message Game to improve students' understanding in learning English. In line with the research objectives, this study uses the CAR (Classroom Action Research) method with a qualitative approach. The research subjects were 32 students from class VIII G who were given the action. The method of data collection is by using a list of observations and oral tests. Data analysis techniques include descriptive and percentage analysis. Descriptive analysis was used to analyze the data items written in the lesson plans, while the percentage was used to analyze students' answers to the oral and written tests. In this study, it was found that the use of the Chain Message Game was able to improve students' understanding in learning, besides that the use of the Chain Message Game was also able to increase student activity, enthusiasm, writing, speaking and listening skills of students in learning English.